Keberkesanan pembayaran semula pembiayaan dana usahawan Perbadanan Kemajuan Negeri Kedah (PKNK) - Saidah, Md Alwi (2020)
Entrepreneurship is one of the most important companents thet could alleviate the nation from the poverty trap. Several initiatives have been adopted by the Malaysia government to help local entreprenuers such as providing loans and also through entrepreneurship programmes. A scheme established by Perbadanan Kemajauan Negeri Kedah (PKNK) - namely “Entrepreneur Loans” has been introduced to enhance entrepreneurship development. Hence this study is to establish and learning the issues related to the financial loans provided by PKNK. The objective of the study is to determine the failure of the repayment of entrepreneur loans. The study is also to determine the significant relationship related to the issues, attitude and factors that influence the effectiveness on the repayment of entrepreneur loans provided by PKNK. This study has adopted the quantitative approach by collecting all data through question aires. There are three important findings in this study based on the set objectives namely (1) the relationship between demographic and the success rate on the repayment of the entrepreneur loans. (2) the relationship between attitude and issues face by the borrowers with affect the repayment of the entrepreneur loans. (3) the relationship between the program organized by PKNK related to the success rate on the repayment of the entrepreneur loans. The findings showed that there was a positive and significant relationship between issues, attitude and program organized by PKNK in relation to the success rate on the repayment of the entrepreneur loans. Conclusively most respondents were concern on the failure of the repayment of loans to PKNK. It clearly demonstrate that the respondents have positive attitude and commitment towards the repayment of entrepreneur loans to PKNK. In addition the program organized by PKNK clearly have positive significant toward to the increase on the success rate on the repayment of the entrepreneur loans.